تأثير استراتيجية التعليم الريادي في تنمية ثقافة ريادة الاعمال لدى الطلبة الجامعيين - علويط، أميرة; فرعون ،امحمد; بولويز ،عبد الوافي (جامعة الوادي University of Eloued, 2025)
This study aims to analyze the impact of the entrepreneurial education strategy adopted by Algeria to foster an entrepreneurial culture among university students in higher education institutions. The study was conducted on a sample consisting of 9 entrepreneurship development centers affiliated with various universities in Algeria, using statistical methods such as the Mann-Whitney test and Kruskal-Wallis test through the SPSS V25 software. The results showed a positive correlation between the formal entrepreneurship training programs offered and the performance of faculty members in fostering an entrepreneurial culture among students, while the impact of pedagogical methods used in teaching entrepreneurship and related metrics was negative. Based on these findings, the study recommends improving entrepreneurship education by enhancing the practical approach in educational programs, providing financial support and incentives for faculty members to encourage their contributions, and establishing a flexible timetable for activities organized by entrepreneurship development centers, especially for summer activities
The impact of entrepreneurial education strategy on developing an entrepreneurial culture among university students in asample of higher education institutions in Algeria.
مقال
Keywords: التعليم الريادي; ريادة الاعمال; مراكز تطوير المقاولاتية; Entrepreneurship Education; Entrepreneurship; Entrepreneurship Development Centers